2006
DOI: 10.1038/sj.ijir.3901447
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet improves erectile function in subjects with the metabolic syndrome

Abstract: Men with the metabolic syndrome demonstrate an increased prevalence of erectile dysfunction (ED). In the present study, we tested the effect of a Mediterranean-style diet on ED in men with the metabolic syndrome. Men were identified in our database of subjects participating in controlled trials evaluating the effect of lifestyle changes and were included if they had a diagnosis of ED associated with a diagnosis of metabolic syndrome, complete follow-up in the study trial, and intervention focused mainly on die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 35 publications
2
94
0
1
Order By: Relevance
“…The connection between diet and systemic inflammatory tone has often been suggested (70,71). Several studies have investigated potential single-meal effects on markers of inflammation, with most studies using HFMs.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between diet and systemic inflammatory tone has often been suggested (70,71). Several studies have investigated potential single-meal effects on markers of inflammation, with most studies using HFMs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Lifestyle, metabolism and erectile function DR Meldrum et al including various combinations of the listed interventions, 50 such as the favorable effects on ED of combining testosterone and sildenafil, 36 or of the Mediterranean diet, which increases intakes of omega-3's, antioxidants and folic acid. 74 …”
Section: Reduction Of Inflammation Improves Endothelial Function and Edmentioning
confidence: 99%
“…15 It is reported that ED may affect obese men, especially both in younger 16 or in those older men with co-morbidities, 17 and that tailored diet is able to restore sexual function when metabolic syndrome is present. 18 Accordingly, the origin of ejaculatory complaints in obese men is poorly investigated. An interesting association between obesity and lifelong PE exists, and some authors reported that patients with lifelong PE were leaner than the healthy control cases, and the prevalence of obesity was lower in the PE group than in the control group.…”
Section: Discussionmentioning
confidence: 99%